Importance of physiotherapy in patients with Alzheimer's (Research, Society and Development, 2023)
Since, physiotherapy is crucial in the treatment of Alzheimer's disease, with an emphasis on early detection, reducing symptoms and minimizing the impacts of the disease. Based on this premise, the objective of the present study was to identify the benefits of physiotherapy in Alzheimer's disease with emphasis on early diagnosis, reduction of symptoms and minimization of the impacts of the pathology, aiming at functional improvement and resulting in improved quality of life. This study in question is a narrative literature review with a descriptive and explanatory character. To conduct the review, literature searches were carried out in several databases, such as Scielo, PubMed, LiLACS, Corporate Sites, and in the physical and digital library collection of Faculdade Integrada Carajás, addressing Alzheimer's Disease, its relationship with aging and the treatments available for this pathology. It is evident that physiotherapy plays a fundamental role in coping with Alzheimer's Disease (AD), covering all its phases. Physiotherapeutic intervention, focused on specific physical exercises, seeks not only to delay the harmful effects of the disease, but also to provide comprehensive benefits, including the maintenance of cognitive functions, balance, independence and quality of life for patients. The individualized approach, highlighted by several authors, recognizes the complexity of AD and the importance of considering the particularities of each patient. From the initial phase to the advanced stages of the disease, physiotherapy aims to meet specific needs, providing preventive, therapeutic and palliative care.